1985
DOI: 10.1080/18811248.1985.9735650
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Behaviors of Nuclear Grade Graphite in Commercial Reactor, (II) Thermal and Physical Properties

Abstract: Thermal conductivity, electrical resistivity and stored energy were measured for Pechiney nuclear grade graphite irradiated in the temperature range 220--400°C up to the maximum neutron fluence 2 . 2~ 1O2O n/cm2(E>0.85 MeV) in the environment of a carbon dioxide in a commercial reactor. Thermal conductivity decreased, electrical resistivity and stored energy increased owing to neutron irradiation and their changes were larger for the samples irradiated a t lower temperatures.A linear relation between stored en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a fusion environment, rigorous conditions such as fast neutron irradiation and thermal shock give rise to diverse changes in micro-/surface structures and physical/mechanical properties including bulk density, coefficient of thermal expansion, thermal conductivity, Young's modulus, and Poisson's ratio [5][6][7][8]. Indeed, Theodosiou et al showed a reduction of crystalline size by ion irradiation [9], and Chi et al observed an increased porosity of graphite after 3 MeV C + ion irradiation [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a fusion environment, rigorous conditions such as fast neutron irradiation and thermal shock give rise to diverse changes in micro-/surface structures and physical/mechanical properties including bulk density, coefficient of thermal expansion, thermal conductivity, Young's modulus, and Poisson's ratio [5][6][7][8]. Indeed, Theodosiou et al showed a reduction of crystalline size by ion irradiation [9], and Chi et al observed an increased porosity of graphite after 3 MeV C + ion irradiation [10].…”
Section: Introductionmentioning
confidence: 99%